PENGEMBANGAN STRATEGI TANDUR MENGGUNAKAN MEDIA E-LEARNING DALAM MENGONVERSI TEKS CERITA PENDEK MENJADI TEKS DRAMA - Nuriana Indah Sari (LOA: Jurnal Ketatabahasaan dan Kesusastraan, 2019)
This study aims to describe about the plan, implementation, evaluation, and effectiveness of TANDUR (Tumbuhkan, Alami, Namai, Demonstrasikan, Ulangi, dan Rayakan) strategy development through e-learning media in converting texts of short story into drama. It uses research and development method (R & D), with reference to the model of Borg and Gall, which creates a product of learning strategy. It will be elaborated in the form of book with a lesson plan and auto play for the instruction of drama text writing. The result shows that the development consists of some stages, namely designing, validating, revising, testing, evaluating, and final testing. Those stages bring out the effectiveness of e-learning TANDUR strategy in enhancing comprehension, participation, and students’ behavior in the learning process. The validators state that it creates a very good product of its instructional design (87,55%) and its instructional media (82%).